Apolipoproteins (apoproteins) and LPL variation in Mennonite populations of Kansas and Nebraska - Demarchi, Dario (2005)
Apoproteins (also known as apolipoproteins) have been studied extensively because of their role in lipid transport, association between specific genotypes and elevated serum lipid levels, and increased risk of heart disease. There is considerable genetic variation in the geographic distributions of these markers, with a north-south cline of the APOE*4 allele observed in Europe by Lucotte et al. ([1997] Hum Biol 69:253–262). This study compares the frequencies of seven APO (APOA1 75 bp, APOA1 þ83 bp, APOB Ins/Del, APOB XbaI, APOC3 SstI, and APOE) and LPL loci in Mennonite populations from Kansas and Nebraska. In total, 277 individuals were sampled from Goessel, Meridian, Garden View, and Lone Tree in 2002–2004. In addition, DNA samples that were collected in 1981 from Henderson, Nebraska, were genotyped for the seven APO and LPL loci. Of the seven APO and LPL loci tested, only one locus, APOB XbaI, departed significantly from Hardy-Weinberg equilibrium, with an unexpected excess of observed heterozygotes. The frequencies of the several APO loci are unique among the Mennonites, separating them from other European populations. A bidimensional scaling representation of Reynold’s coancestry distances based on allelic frequencies of the seven APO and LPL markers in five Mennonite congregations fails to represent schematically the known patterns of fission. It is unclear whether the observed patterns are due to selection operating on these loci or whether genetic drift, small populations sizes, or a lack of statistical power of these biallelic loci distort the observed genetic relationship among congregations.